2019
DOI: 10.1186/s12962-019-0178-3
|View full text |Cite
|
Sign up to set email alerts
|

Model-based cost-effectiveness analysis of external beam radiation therapy for the treatment of localized prostate cancer: a systematic review

Abstract: Background External beam radiotherapy is the recommended but expensive treatment option for localized prostate cancer. Prostate cancer is the most common cancer in men worldwide. A cost-effectiveness study is needed given the excessive cost of radiotherapy treatment and the high prevalence of prostate cancer. The aim of this systematic review was to assess and identify studies that examined model based economic evaluation of external beam radiation therapy for the treatment of localized prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…Costs and quality of life data will be collected as well, to identify cost-effective MR-Linac treatment strategies compared to alternative treatments. This is particularly useful in the field of prostate cancer, where many treatment modalities with comparable outcomes, but with different costs are available ( 54 ). Further MR-Linac impact studies can also provide insights into its effects on prostate cancer treatment allocation and hospital infrastructure.…”
Section: Discussion and Implications For Practice And Future Researchmentioning
confidence: 99%
“…Costs and quality of life data will be collected as well, to identify cost-effective MR-Linac treatment strategies compared to alternative treatments. This is particularly useful in the field of prostate cancer, where many treatment modalities with comparable outcomes, but with different costs are available ( 54 ). Further MR-Linac impact studies can also provide insights into its effects on prostate cancer treatment allocation and hospital infrastructure.…”
Section: Discussion and Implications For Practice And Future Researchmentioning
confidence: 99%
“…It has been shown that ultrahypofractionation is associated with lower overall treatment costs than normofractionated 3D conformal or IMRT [17] as well as moderate hypofractionation [18]. In a recent systemic review comprising 12 studies, Abreha et al [19] performed a modelbased cost-effectiveness analysis confirming that ultrahypofractionation is the most effective treatment in terms of overall treatment cost, including prostatectomy.…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…In a recent systemic review comprising 12 studies, Abreha et al. [ 19 ] performed a model-based cost-effectiveness analysis confirming that ultrahypofractionation is the most effective treatment in terms of overall treatment cost, including prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review has explored the costeffectiveness of different radiotherapy modalities [45]. The authors included all published articles with a full economic evaluation and found three articles comparing SBRT with IMRT.…”
Section: Cost-effectivenessmentioning
confidence: 99%